Pengaruh Media Pembelajaran Berbasis Teknologi Informasi Dalam Proses Pembelajaran IPS Terhadap Peningkatan Hasil Belajar Siswa SMP Negri 02 Batanghari - Arista Wati; Nur Asyiyatul Muthiy; Siti Alfinah; Wellfarina Hamer (JEE (Jurnal Edukasi Ekobis), 2019)
The purpose of this study is intended to determine whether there is an influence of the use of IT-based learning media in the social studies learning process to improve student learning outcomes in SMP Negeri 02 Batanghari. This research uses a quantitative method of experimental explanation. The subjects of this study were students of class IX with a sample of 30 students. The results showed the average value of the use of the two learning media was statistically tested using the t test statistic by comparing the results of t arithmetic with t table. The results of t count for the average learning outcomes of Social Sciences is 1.77093 with a significance of 0,000 while the results of t tables on social studies learning are 2.16037. This is based on significance (α = 5%) and degree of freedom (degree of fridom) 13 (n (15) -2)). Therefore, the significance for the two-tailed test is 0,000 0.25. So Hₒ is rejected because the two average social studies learning outcomes using conventional learning media with social studies based on information technology are really significantly different.Keywords: Conventional Social Studies Learning Media, IT Media and Learning Outcomes